Metal-organic frameworks as competitive materials for non-linear optics - Mingabudinova, L R; Vinogradov, V V; Milichko, V A; Hey-Hawkins, E; Vinogradov, A V (Chemical Society reviews, 2016)
The last five years have witnessed a huge breakthrough in the creation and the study of the properties of a new class of compounds - metamaterials. The next stage of this technological revolution will be the development of active, controllable, and non-linear metamaterials, surpassing natural media as platforms for optical data processing and quantum information applications. However, scientists are constantly faced with the need to find new methods that can ensure the formation of quantum and non-linear metamaterials with higher resolution. One such method of producing metamaterials in the future, which will provide scalability and availability, is chemical synthesis. Meanwhile, the chemical synthesis of organized 3D structures with a period of a few nanometers and a size of up to a few millimeters is not an easy task and is yet to be resolved. The most promising avenue seems to be the use of highly porous structures based on metal-organic frameworks that have demonstrated their unique properties in the field of non-linear optics (NLO) over the past three years. Thus, the aim of this review is to examine current progress and the possibilities of using metal-organic frameworks in the field of non-linear optics as chemically obtained metamaterials of the future. The review begins by presenting the theoretical principles of physical phenomena represented by mathematical descriptions for clarity. Major attention is paid to the second harmonic generation (SHG) effect. In this section we compare inorganic single crystals, which are most commonly used to study the effect in question, to organic materials, which also possess the required properties. Based on these data, we present a rationale for the possibility of studying the non-linear optical properties of metal-organic structures as well as describing the use of synthetic approaches and the difficulties associated with them. The second part of the review explicitly acquaints the reader with a new class of materials which successfully combines the positive properties of organic and inorganic materials. Using recently synthesized metal-organic frameworks and coordination polymers in the field of non-linear optics as an example, we consider synthetic approaches used for obtaining materials with desired properties and the factors to be considered in this case. Finally, probable trends towards improving the quality of the synthesized materials with regards to their further use in the field of non-linear optical effects are described.